Socio‐economic disparity, access to care and patient‐relevant outcomes after kidney allograft failure. (14th September 2021) - Wong, Yun Hui Sheryl; Wong, Germaine; Johnson, David W.; McDonald, Stephen; Clayton, Philip; Boudville, Neil; Viecelli, Andrea K.; Lok, Charmaine; Pilmore, Helen; Hawley, Carmel; Roberts, Matthew A.; Walker, Rachael; et al.
SUMMARY: Social disparity is a major impediment to optimal health outcomes after kidney transplantation. In this study, we aimed to define the association between socio‐economic status (SES) disparities and patient‐relevant outcomes after kidney allograft failure. Using data from the Australia and New Zealand Dialysis and Transplant registry, we included patients with failed first‐kidney allografts in Australia between 2005 and 2017. The association between residential postcode‐derived SES in quintiles (quintile 1‐most disadvantaged areas, quintile 5‐most advantaged areas) with uptake of home dialysis (peritoneal or home haemodialysis) within the first 12‐months post‐allograft failure, repeat transplantation and death on dialysis were examined using competing‐risk analysis. Of 2175 patients who had experienced first allograft failure, 417(19%) and 505(23%) patients were of SES quintiles 1 and 5, respectively. Compared to patients of quintile 5, quintile 1 patients were less likely to receive repeat transplants (adjusted subdistributional hazard ratio [SHR] 0.70, 95%CI 0.55–0.89) and were more likely to die on dialysis (1.37 [1.04–1.81]), but there was no association with the uptake of home dialysis (1.02 [0.77–1.35]). Low SES may have a negative effect on outcomes post‐allograft failure and further research is required into how best to mitigate this. However, small‐scale variation within SES cannot be accounted for in this study. Abstract : Patients with kidney failure from higher SES was associated with increased likelihood of repeated transplantation and a lower risk of all‐cause mortality on dialysis following first kidney allograft failure, but there was no association with the early uptake of home dialysis treatment.